Relationship between ROS production, MnSOD activation and periods of fasting and re-feeding in freshwater shrimp Neocaridina davidi (Crustacea, Malacostraca) - Agnieszka Włodarczyk; Grażyna Wilczek; Piotr Wilczek; Sebastian Student; Anna Ostróżka; Monika Tarnawska; Magdalena Rost-Roszkowska (PeerJ, 2019)
The middle region of the digestive system, the midgut of freshwater shrimp Neocaridina davidi is composed of a tube-shaped intestine and the hepatopancreas formed by numerous caeca. Two types of cells have been distinguished in the intestine, the digestive cells (D-cells) and regenerative cells (R-cells). The hepatopancreatic tubules have three distinct zones distinguished along the length of each tubule—the distal zone with R-cells, the medial zone with differentiating cells, and the proximal zone with F-cells (fibrillar cells) and B-cells (storage cells). Fasting causes activation of cell death, a reduction in the amount of reserve material, and changes in the mitochondrial membrane potential. However, here we present how the concentration of ROS changes according to different periods of fasting and whether re-feeding causes their decrease. In addition, the activation/deactivation of mitochondrial superoxide dismutase (MnSOD) was analyzed. The freshwater shrimps Neocaridina davidi (Crustacea, Malacostraca, Decapoda) were divided into experimental groups: animals starved for 14 days, animals re-fed for 4, 7, and 14 days. The material was examined using the confocal microscope and the flow cytometry. Our studies have shown that long-term starvation increases the concentration of free radicals and MnSOD concentration in the intestine and hepatopancreas, while return to feeding causes their decrease in both organs examined. Therefore, we concluded that a distinct relationship between MnSOD concentration, ROS activation, cell death activation and changes in the mitochondrial membrane potential occurred.